Eksplorasi Faktor Penerimaan Blockchain oleh Pengusaha UMKM - Junardi Junardi (Journal of Science and Technology: Alpha, 2025)
This study aims to explore the factors influencing the acceptance of blockchain technology among entrepreneurs of Micro, Small, and Medium Enterprises (MSMEs). Blockchain technology offers various advantages, such as transparency, efficiency, and transaction security, which have the potential to enhance the competitiveness of MSMEs. However, the adoption rate remains relatively low, particularly in developing countries, including Indonesia. Using a qualitative approach, this research involves in-depth interviews with MSME entrepreneurs from various sectors to understand their perceptions, barriers, and potential applications of blockchain in their business activities. The findings indicate that the main factors influencing blockchain acceptance include technological understanding, trust in the system, infrastructure readiness, regulatory support, and perceived benefits and costs. This study provides insights on how MSMEs can be encouraged to adopt blockchain technology through education, assistance, and policy reinforcement. These findings are expected to serve as a reference for policymakers, technology providers, and academics in designing strategies that support the implementation of blockchain in the MSME sector.